Assessing explanatory models and health beliefs: An essential but overlooked competency for clinicians. (March 2017) - Dinos, Sokratis; Ascoli, Micol; Owiti, John A.; Bhui, Kamaldeep
Summary: Explanatory models of illness – the way people perceive, interpret and respond to it – are mediated not only by the illness itself, but also by cultural and social contexts. This article discusses recent evidence showing how the exploration of explanatory models can help to shape treatment and outcomes for some of the most common categories of mental illness, and presents case studies illustrating dilemmas clinicians face when their explanatory models differ from those of their patients. It concludes with recommendations on how a culturally sensitive clinical approach based on the exploration of explanatory models during assessment and treatment can be used as an effective way of dealing with the complexity of patients' and families' needs. Learning Objectives: Appreciate the use of explanatory models in clinical practice Understand the relevance of explanatory models in relation to specific diagnostic categories of mental illness Recognise that dilemmas may arise if the explanatory models of the clinician and the patient differ, and be able to manage this tension